Instructional Leadership and Data-Based Planning as Determinants of Teachers’ Performance in Vocational High Schools - Wahyuningsih, Siti; Buchori, Achmad; Wuryandini, Endang (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the effects of instructional leadership and data-driven planning on the performance of public vocational high school (SMK) teachers in Semarang Regency. A quantitative approach was employed using an ex post facto method with a correlational research design. The population consisted of 247 productive/vocational SMK teachers in Semarang Regency. Proportional random sampling was used to ensure representation from each school, resulting in a sample of 156 teachers. Data were collected through closed-ended questionnaires that were tested for validity using Pearson’s product-moment correlation and for reliability using Cronbach’s Alpha to ensure their validity and reliability. The data were analyzed using simple and multiple linear regression with SPSS. The results indicate that instructional leadership partially contributes 18.3% to SMK teacher performance, while data-driven planning contributes 19.8%. Simultaneously, both variables have a combined effect of 26.7%. These findings suggest that improving SMK teacher performance requires effective instructional leadership and well-implemented data-driven planning. Collaboration between learning-centered leadership and effective data utilization and management supports teacher performance in achieving high-quality learning. Teachers are expected to improve their data literacy so that data use is not merely administrative but also analytical and strategic. This study is expected to serve as a reference for education policymakers in designing more effective and sustainable strategies to enhance teacher performance.